2001
DOI: 10.1016/s0893-133x(00)00177-9
|View full text |Cite
|
Sign up to set email alerts
|

Lower Baseline Plasma Cortisol and Prolactin together with Increased Body Temperature and Higher mCPP-Induced Cortisol Responses in Men with Pedophilia

Abstract: There is some evidence that hormonal and serotonergic alterations may play a role in the pathophysiology of paraphilias. The aims of the present study were to examine: 1) baseline plasma cortisol, plasma prolactin, and body temperature; and 2) cortisol, prolactin, body temperature, as well as behavioral responses to metachlorophenylpiperazine (mCPP) The sexual abuse of children (pedophilia) represents a significant proportion of about 25% of all sexual offences (Moller and Bier-Weiss 1995). Between 100,000 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 49 publications
1
18
1
2
Order By: Relevance
“…These findings run somewhat contrary to the findings of Maes, et al (2001) who reported elevated prolactin among pedophiles.…”
Section: )contrasting
confidence: 99%
“…These findings run somewhat contrary to the findings of Maes, et al (2001) who reported elevated prolactin among pedophiles.…”
Section: )contrasting
confidence: 99%
“…Neurochemical findings show that individuals with developmental paedophilia may have a serotonergic disturbance, most likely caused by the decreased activity of the presynaptic serotonergic neurons and hypersensitivity of the serotonin 2 postsynaptic receptors (Maes & Meltzer, 1996;Maes et al, 2001). Previous reports (Moller & Bier-Weiss, 1995) have shown that disorders in serotonin metabolism and increased sympathoadrenal system activity are related to aggression or violence and impulse control disorder.…”
Section: Acquired Paedophilia Is Not Developmental Paedophiliamentioning
confidence: 93%
“…Previous reports (Moller & Bier-Weiss, 1995) have shown that disorders in serotonin metabolism and increased sympathoadrenal system activity are related to aggression or violence and impulse control disorder. Maes et al (2001) hypothesize that disorders in the serotonergic neurons and increased catecholaminergic turnover in individuals with developmental paedophilia may lead these individuals to aggression (persuasion, coercion or physical force) or sexual violence (damage to the physical integrity of the victims) (Cosyns, 1999;Greenberg, Bradford, & Curry, 1996). In terms of the neurodevelopmental hypothesis, De Ridder et al (2009) have advanced that the two most important functional neuroanatomic models of individuals with developmental paedophilia involve frontal-executive dysfunction or temporo-limbic dysfunction, or combinations of both.…”
Section: Acquired Paedophilia Is Not Developmental Paedophiliamentioning
confidence: 99%
“…200 Some potentially important physiological anomalies have been observed in pedophiles. Right temporal lobe hypometabolism has been identified in adult pedophiles, 201 as have lower baseline cortisol levels 202 and monoaminergic dysfunction. 203 Although pedophilia is not well studied, some researchers believe that neurological deficits, chromosome aberration, or early childhood abuse or sexual experience may imprint desire onto inappropriate outlets.…”
Section: Behavioral Traitsmentioning
confidence: 99%